POSS hybrid hydrogels: A brief review of synthesis, properties and applications. (15th January 2021) - Liu, Siju; Guo, Renqi; Li, Chuang; Lu, Cuifen; Yang, Guichun; Wang, Feiyi; Nie, Junqi; Ma, Chao; Gao, Meng
Graphical abstract: Polyhedral oligomeric silsesquioxane (POSS) is non-toxic and tasteless, and has good biocompatibility, stability and other characteristics, which is used as a "nano-building" unit for the preparation of new organic–inorganic hybrid materials. POSS nanoparticles can be introduced into hydrogels via simple and easy methods such as physical blending, ionic interaction and covalent bonding to prepare POSS hybrid hydrogels with the rigidity of inorganic materials and the processability of organic materials. These excellent POSS hybrid hydrogels can be used in cell culture, bone regeneration, drug delivery and catalytic carriers. This brief review summarized the preparation methods of POSS hybrid hydrogels and related application research, and discussed some future applications of the hybrid hydrogels. Abstract: Polyhedral oligomeric silsesquioxane (POSS) is non-toxic and tasteless, and has good biocompatibility, stability and other characteristics, which is used as a "nano-building" unit for the preparation of new organic–inorganic hybrid materials. POSS nanoparticles can be introduced into hydrogels via simple and easy methods such as physical blending, ionic interaction and covalent bonding to prepare POSS hybrid hydrogels with the rigidity of inorganic materials and the processability of organic materials. These excellent POSS hybrid hydrogels can be used in cell culture, bone regeneration, drug delivery and catalytic carriers. This brief review summarized the preparation methods of POSS hybrid hydrogels and related application research, and discussed some future applications of the hybrid hydrogels.